2006
DOI: 10.1111/j.1365-2664.2006.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of plant invasions mediated by frugivore interactions

Abstract: Summary1. Some of the most damaging invasive plants are dispersed by frugivores and this is an area of emerging importance in weed management. It highlights the need for practical information on how frugivores affect weed population dynamics and spread, how frugivore populations are affected by weeds and what management recommendations are available. 2. Fruit traits influence frugivore choice. Fruit size, the presence of an inedible peel, defensive chemistry, crop size and phenology may all be useful traits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
173
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(177 citation statements)
references
References 116 publications
(134 reference statements)
1
173
0
Order By: Relevance
“…10,no. 3 of the frugivores' preferred habitat within fragmented landscapes (Buckley et al 2006). Mandon-Dalger et al (2004) observed a possible synergistic interaction between alien birds and alien weeds, including Schinus in Reunion Island.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…10,no. 3 of the frugivores' preferred habitat within fragmented landscapes (Buckley et al 2006). Mandon-Dalger et al (2004) observed a possible synergistic interaction between alien birds and alien weeds, including Schinus in Reunion Island.…”
Section: Discussionmentioning
confidence: 98%
“…Linnebjerg et al 2009). Information on frugivores and the role of different dispersers should be considered at all stages of weed management (Buckley et al 2006). An opposite perspective rises in areas of natural occurrence of Schinus in South America.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are increasing efforts to collect information on the potential dispersers of invasive plant species [12] and on the plants dispersed by introduced animals [13]. However, rigorous information on the entire species assemblages of plants, seed dispersers and their interactions is still rarely available [14]. Even when such studies exist, they have mainly considered birds, with reptiles and mammals receiving much less attention [15].…”
Section: Introductionmentioning
confidence: 99%